2010
DOI: 10.1016/j.crohns.2009.11.002
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal carcinoma and preceding fistula in Crohn's disease

Abstract: Colorectal carcinoma is frequently associated with the presence of longstanding anorectal fistula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
0
16
0
Order By: Relevance
“…Twenty‐one studies contributed data specific for UC, while only five studies for CD . The reduction in CRN risk associated with 5‐ASA use was 50% among UC patients (RR = 0.50, 95% CI: 0.38–0.64), but weaker and nonsignificant among patients with CD (RR = 0.76, 95% CI: 0.43–1.33) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Twenty‐one studies contributed data specific for UC, while only five studies for CD . The reduction in CRN risk associated with 5‐ASA use was 50% among UC patients (RR = 0.50, 95% CI: 0.38–0.64), but weaker and nonsignificant among patients with CD (RR = 0.76, 95% CI: 0.43–1.33) (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Twenty‐one studies evaluated the association of 5‐ASA with CRC risk, while five studies reported data for dysplasia. Exposure to 5‐ASA was significantly associated with a protective effect against both outcomes (cancer: RR = 0.58, 95% CI: 0.45–0.74, Figure ; dysplasia: RR = 0.54, 95% CI: 0.35–0.84, Figure ) (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A cohort study showed that the severity of microscopic inflammation over time is an independent risk factor for developing advanced colorectal neoplasia among patients with longstanding ulcerative colitis (25). In addition, in Crohn's disease patients, perianal disease, bypasses and strictures may be sites of increased risk for neoplastic transformation (26,27). These findings indicate that, in IBD patients, chronic intestinal inflammation may be the leading cause of CAC.…”
Section: Discussionmentioning
confidence: 99%